Mutation-specific effects in germline transmission of pathogenic mtDNA variants. Issue 7 (30th May 2018) - Otten, Auke B C; Sallevelt, Suzanne C E H; Carling, Phillippa J; Dreesen, Joseph C F M; Drüsedau, Marion; Spierts, Sabine; Paulussen, Aimee D C; de Die-Smulders, Christine E M; Herbert, Mary; Chinnery, Patrick F; Samuels, David C; Lindsey, Patrick; et al.
Abstract: STUDY QUESTION: Does germline selection (besides random genetic drift) play a role during the transmission of heteroplasmic pathogenic mitochondrial DNA (mtDNA) mutations in humans? SUMMARY ANSWER: We conclude that inheritance of mtDNA is mutation-specific and governed by a combination of random genetic drift and negative and/or positive selection. WHAT IS KNOWN ALREADY: mtDNA inherits maternally through a genetic bottleneck, but the underlying mechanisms are largely unknown. Although random genetic drift is recognized as an important mechanism, selection mechanisms are thought to play a role as well. STUDY DESIGN, SIZE, DURATION: We determined the mtDNA mutation loads in 160 available oocytes, zygotes, and blastomeres of five carriers of the m.3243A>G mutation, one carrier of the m.8993T>G mutation, and one carrier of the m.14487T>C mutation. PARTICIPANTS/MATERIALS, SETTING, METHODS: Mutation loads were determined in PGD samples using PCR assays and analysed mathematically to test for random sampling effects. In addition, a meta-analysis has been performed on mutation load transmission data in the literature to confirm the results of the PGD samples. MAIN RESULTS AND THE ROLE OF CHANCE: By applying the Kimura distribution, which assumes random mechanisms, we found that mtDNA segregations patterns could be explained by variable bottleneck sizes among all our carriers (moment estimates ranging from 10 to 145). Marked differences in the bottleneck size would determine the probability that a carrier produces offspring with mutations markedly different than her own. We investigated whether bottleneck sizes might also be influenced by non-random mechanisms. We noted a consistent absence of high mutation loads in all our m.3243A>G carriers, indicating non-random events. To test this, we fitted a standard and a truncated Kimura distribution to the m.3243A>G segregation data. A Kimura distribution truncated at 76.5% heteroplasmy has a significantly better fit ( P -value = 0.005) than the standard Kimura distribution. For the m.8993T>G mutation, we suspect a skewed mutation load distribution in the offspring. To test this hypothesis, we performed a meta-analysis on published blood mutation levels of offspring–mother (O–M) transmission for the m.3243A>G and m.8993T>G mutations. This analysis revealed some evidence that the O–M ratios for the m.8993T>G mutation are different from zero ( P -value <0.001), while for the m.3243A>G mutation there was little evidence that the O–M ratios are non-zero. Lastly, for the m.14487T>G mutation, where the whole range of mutation loads was represented, we found no indications for selective events during its transmission. LARGE SCALE DATA: All data are included in the Results section of this article. LIMITATIONS, REASON FOR CAUTION: The availability of human material for the mutations is scarce, requiring additional samples to confirm our findings. WIDER IMPLICATIONS OF THE FINDINGS: Our data show that non-random mechanisms are involved during mtDNA segregation. We aimed to provide the mechanisms underlying these selection events. One explanation for selection against high m.3243A>G mutation loads could be, as previously reported, a pronounced oxidative phosphorylation (OXPHOS) deficiency at high mutation loads, which prohibits oogenesis (e.g. progression through meiosis). No maximum mutation loads of the m.8993T>G mutation seem to exist, as the OXPHOS deficiency is less severe, even at levels close to 100%. In contrast, high mutation loads seem to be favoured, probably because they lead to an increased mitochondrial membrane potential (MMP), a hallmark on which healthy mitochondria are being selected. This hypothesis could provide a possible explanation for the skewed segregation pattern observed. Our findings are corroborated by the segregation pattern of the m.14487T>C mutation, which does not affect OXPHOS and MMP significantly, and its transmission is therefore predominantly determined by random genetic drift. Our conclusion is that mutation-specific selection mechanisms occur during mtDNA inheritance, which has implications for PGD and mitochondrial replacement therapy. STUDY FUNDING/COMPETING INTEREST(S): This work has been funded by GROW-School of Oncology and Developmental Biology. The authors declare no competing interests.